GERAKAN BINA BALITA “SEHAT” DALAM PENCEGAHAN STUNTING DI DESA TELUK KENIDAI KABUPATEN KAMPAR - Alyensi, Fatiyani; Laila, Ani; Susanti, Ari (Jurusan Kebidanan Poltekkes Kemenkes Riau, 2024)
Abstract The National Population and Family Planning Agency (BKKBN) of Riau Province continues to optimize the Toddler Family Development (BKB) program to avoid an increase in stunting or failure to thrive in children under five in Riau Province. Based on a preliminary study by conducting interviews with the responsible midwife in Teluk Kenidai village, it was stated that a Bina Toddler (BKB) has been formed called the